PENGARUH KINERJA PEGAWAI TERHADAP KEPUASAN MASYARAKAT MELALUI VARIABEL INTERVENING KUALITAS PELAYANAN - Suryana, Nia; Paramarta, Vip (Program Studi Magister Manajemen, Direktorat Pascasarjana, Universitas Sangga Buana, 2024)
Quality services will produce public satisfaction with government performance. The aim of this research is to determine the direct and indirect influence of employee performance on community satisfaction through the quality of service in the work unit of the Assistant Deputy for Youth Pioneering at the Ministry of Youth and Sports. The respondents in this research were 30 people who benefited from the activities of the Assistant Deputy for Youth Pioneering. Data collection using the questionnaire method. Meanwhile, the data retrieval technique uses Non-Probability Sampling with a voluntary sampling approach. Data analysis techniques use regression analysis followed by path analysis. The results of the hypothesis test show that employee performance has a significant effect on public satisfaction through service quality. From the f test results, it was obtained that simultaneously employee performance and service quality had a significant effect on public satisfaction. The results of the f-test showed that simultaneously, the performance of the staff and the service quality had a significant influence on public satisfaction.